Destruction of decabromodiphenyl ether during incineration of plastic television housing waste at commercial-scale industrial waste incineration plants. Issue 2 (April 2021) - Kajiwara, Natsuko; Noma, Yukio; Tamiya, Mayumi; Teranishi, Tadashi; Kato, Yuri; Ito, Yugo; Sakai, Shinichi
Abstract: To investigate the destruction of decabromodiphenyl ether (decaBDE) contained in flame-retarded plastics, we conducted a series of co-incineration tests of plastic television (TV) housing waste at two commercial-scale industrial waste incinerators in Japan, one equipped with a rotary kiln furnace and the other with a stoker furnace. At the former, crushed TV housings containing 5.9% (59, 000 mg/kg) decaBDE were mixed at 3.2 wt% with normal industrial waste and incinerated at 1000 °C; at the latter, crushed housings containing 4.9% (49, 000 mg/kg) decaBDE were mixed at 3.6 wt% with normal industrial waste and incinerated at 1100 °C. Destruction efficiencies of over 99.9999% were achieved at both plants, and discharge of brominated dioxins and furans was negligible. More than 70% of the total decaBDE output and 90% of the total bromine output were found in the bottom ash and the fly ash, respectively, suggesting that any undecomposed decaBDE was discharged into the bottom ash and that desorbed bromine was concentrated into the fly ash. Our findings indicate that controlled co-incineration is an environmentally sound method for destruction of decaBDE, but attention should be paid to disposing of the bottom and fly ash in a manner that avoids environmental and human impacts. Graphical Abstract: ga1 Highlights: Co-incineration tests of plastic TV housing waste were conducted at two incinerators. Controlled incineration can sufficiently destroy 59, 000 mg/kg of decaBDE in TV. PBDE destruction efficiencies of >99.9999% were achieved without PBDD/F discharge. Undecomposed decaBDE and desorbed Br were found in bottom and fly ash, respectively.